The impact of magnetic resonance imaging anxiety on treatment adherence - Lei, Lixing; Yang, Xiongxiong; Liu, Nian; Tang, Lingling; He, Xin; Huang, Xiaohua (Frontiers in Psychiatry, 2025)
BackgroundMagnetic resonance imaging (MRI) exams often induce higher levels of patient anxiety compared to other routine examinations due to factors such as enclosed spaces, prolonged immobility, and noise interference. This anxiety may interfere with cognitive function and reduce patients’ willingness to adhere to medical instructions. However, previous research has seldom investigated the impact of MRI anxiety on patients’ treatment adherence.MethodTo address this gap, the current study employs a convenience sampling method to select 495 patients who underwent MRI examinations at a tertiary hospital in Sichuan Province between April and June 2025. We utilize the MRI Anxiety Scale, Loss Aversion Scale, Information Avoidance Scale, and Treatment Adherence Scale to conduct our investigation. Based on the Information asymmetry theory, this study constructs a structural equation model to analyze the relationship between MRI anxiety and treatment adherence, as well as the underlying mechanisms.ResultThe results show that MRI anxiety is significantly negatively correlated with treatment adherence and significantly positively correlated with both loss aversion and information avoidance. Loss aversion and information avoidance partially mediate the association between MRI anxiety and treatment adherence. The findings suggest that higher levels of MRI anxiety are associated with lower treatment adherence, with loss aversion and information avoidance behaviors potentially contributing to this relationship.ConclusionTherefore, clinical practice should include targeted interventions addressing loss aversion and information avoidance, such as optimizing risk communication strategies and providing structured informational support, to alleviate anxiety and improve treatment adherence, thereby providing a theoretical foundation and practical pathway to enhance MRI examination outcomes.